Oil-treated pleated fibrous air filters for motor vehicle engine intake application. (February 2020) - Maddineni, Ajay Kumar; Das, Dipayan; Damodaran, Ravi Mohan
In this work, oil-treated pleated fibrous air filters were developed, characterized, and evaluated for motorcycle engine intake application. The effect of pleat geometry on the filtration performance was examined. Pleat pitch and pleat height were found to play important roles in determining the filtration efficiency, pressure drop, and dust holding capacity. A pleated fibrous filter prepared with optimum levels of pleat pitch and pleat height showed the best filtration performance. The treatment to the pleated filter by viscous oil yielded remarkably higher dust holding capacity and filtration efficiency, both at cleaned and clogged conditions. A statistical analysis revealed that the weight of oil played a significant role in deciding the filtration performance. The oil-treated pleated filter was installed in a commercial air intake system and its filtration performance was assessed. The filter element displayed a significant delay in evolution of pressure drop during dust loading as compared to the untreated one. However, the difference in filtration efficiency between the oil-treated and untreated filter elements was not found to be too high. Nevertheless, both of them met the standard filtration performance as per the best practices followed by the automotive industry. Overall, the oil treatment to cellulosic filters was found to be highly advantageous for motorcycle application. Practical implications of such air filter system were discussed in terms of service life, fuel consumption, and CO2 emission during filter life time.